Analysis of Fee Based Income Recognition in E-Money Transactions on Muamalat DIN Based on Psak 72 - Nadyah, Dyah; Idayanti, Rini; Hasbi, Hartas (MALIA: Journal of Islamic Banking and Finance, 2026)
This study examines the calculation and recognition of Fee Based Income from e-money transactions in the Muamalat Digital Islamic Network (DIN) application at Bank Muamalat KCP Bone based on PSAK 72. The purpose of this study is to analyze how Fee Based Income is calculated and recognized in digital banking services while ensuring that the practice remains in line with accounting standards and sharia principles. This research uses a descriptive qualitative approach with field research methods. Data were collected through interviews with branch supervisors, customer service officers, and tellers, supported by documentation of e-money transactions carried out through the Muamalat DIN application. The results show that the calculation of Fee Based Income is performed automatically through a system integrated with the bank’s core banking system, so branch employees are not involved in manual calculations. The administrative fee is clearly displayed before the customer confirms the transaction, reflecting transparency in service delivery. Revenue recognition is carried out only after the transaction has been successfully completed and the customer has received the intended service. This practice is consistent with PSAK 72, particularly the principle that revenue is recognized after performance obligations have been fulfilled. The findings also indicate that the Muamalat DIN digital transaction system contributes positively to stable non-financing income, strengthens the reliability of fee recording, and maintains compliance with sharia principles in banking services at the branch level.